MENGENAL KITAB SUNAN AL-TIRMIDZI (KITAB HADITS HASAN) - Hasan Su’aidi (UIN K.H. Abdurrahman Wahid Pekalongan, 2010)
﻿As one of Hadith books that is included in the six main Hadits books (kutub al-sittah), Sunan Tirmidzi has a different writing methodology from other main Hadith books. It can be seen from the existence of quality valuing of Hadiths written in the book that is rarely done by other writers of Hadith books. Besides, the existence of Hadith classification into three classifications, i.e. shahih, hasan and da’if that has not yet been known, make al-Tirmidzi and his Hadith book interesting to study further.